Introducing an Intervention Model for Fostering Affective Involvement with Persons who Are Congenitally Deafblind. (January 2014) - Martens, Marga A. W.; Janssen, Marleen J.; Ruijssenaars, Wied A. J. J. M.; Riksen-Walraven, J. Marianne
The article presented here introduces the Intervention Model for Affective Involvement (IMAI), which was designed to train staff members (for example, teachers, caregivers, support workers) to foster affective involvement during interaction and communication with persons who have congenital deaf-blindness. The model is theoretically underpinned, and practical implications and preliminary implementation findings are discussed.